Chemical abundance of z~ 6 quasar broad-line regions in the XQR-30 sample. Issue 2 (11th April 2022) - Lai, Samuel; Bian, Fuyan; Onken, Christopher A; Wolf, Christian; Mazzucchelli, Chiara; Bañados, Eduardo; Bischetti, Manuela; Bosman, Sarah E I; Becker, George; Cupani, Guido; D'Odorico, Valentina; Eilers, Anna-Christina; et al.
ABSTRACT: The elemental abundances in the broad-line regions of high-redshift quasars trace the chemical evolution in the nuclear regions of massive galaxies in the early Universe. In this work, we study metallicity-sensitive broad emission-line flux ratios in rest-frame UV spectra of 25 high-redshift (5.8 < z < 7.5) quasars observed with the VLT/X-shooter and Gemini/GNIRS instruments, ranging over $\log \left({{M}_{\rm {BH}}/\rm {M}_{\odot }}\right) = 8.4-9.8$ in black hole mass and $\log \left(\rm {L}_{\rm {bol}}/\rm {erg \, s}^{-1}\right) = 46.7-47.7$ in bolometric luminosity. We fit individual spectra and composites generated by binning across quasar properties: bolometric luminosity, black hole mass, and blueshift of the C iv line, finding no redshift evolution in the emission-line ratios by comparing our high-redshift quasars to lower redshift (2.0 < z < 5.0) results presented in the literature. Using cloudy -based locally optimally emitting cloud photoionization model relations between metallicity and emission-line flux ratios, we find the observable properties of the broad emission lines to be consistent with emission from gas clouds with metallicity that are at least 2–4 times solar. Our high-redshift measurements also confirm that the blueshift of the C iv emission line is correlated with its equivalent width, which influences line ratios normalized against C iv . When accounting for the C iv blueshift, we find that the rest-frame UV emission-line flux ratios do not correlate appreciably with the black hole mass or bolometric luminosity.